Brazilian agribusiness: Investment in vertical farming as a competitive advantage - Silva , Beatriz Campanha; Canovas, Bianca Allegretti; Almeida, Gabriella Luiza Garcia de; Antônio, Lorena Nocente de; Fernandez, Rodrigo Dias (Seven Editora, 2024)
Agriculture is one of the main economic activities in the world, it has been growing strongly with its strategy of ensuring the availability of food, guaranteeing an important source of income. Faced with the global challenge of growing food for a growing world population, the world's largest agricultural producers have secured a significant increase with different technological investments over time, diversifying field production in recent decades. Vertical farming, used mainly in large urban centers, has been seen as the technology of the agronomic future to meet consumer demands. During the development of the article, some research methods were used, such as documentary, field research and economic-financial information, as they present advantages such as: standardization of the crop and root environment, drastic reduction in the use of water, better control of vegetative growth, greater production, quality and precocity, in addition to greater possibilities of mechanization and automation of the crop. Thus obtaining high rates of return. It can be concluded, then, that these technologies come in the sense of positioning themselves as a solution to the main problems that arise in agriculture, lack of land for planting, for example, soil in inadequate conditions, population growth, global warming, pollution, and food waste. From this, the purpose of this work is to address the main innovations brought by technological innovation to agriculture. DOI:https://doi.org/10.56238/sevened2023.006-101